Frequent silencing of RASSF1A by DNA methylation in thymic neuroendocrine tumours. (September 2017) - Kajiura, Koichiro; Takizawa, Hiromitsu; Morimoto, Yuki; Masuda, Kiyoshi; Tsuboi, Mitsuhiro; Kishibuchi, Reina; Wusiman, Nuliamina; Sawada, Toru; Kawakita, Naoya; Toba, Hiroaki; Yoshida, Mitsuteru; Kawakami, Yukikiyo; et al.
Highlights: Genome-wide screening of DNA methylation in thymic epithelial tumours. RASSF1A is one of the significantly methylated genes in thymic endocrine tumours. The expression status of RASSF1A is dysregulated by methylation in promoter region. Abstract: Objectives: Aberrant methylation of promoter CpG islands (CGIs) of tumour suppressor genes is a common epigenetic mechanism underlying cancer pathogenesis. The methylation patterns of thymic tumours have not been studied in detail since such tumours are rare. Herein, we sought to identify genes that could serve as epigenetic targets for thymic neuroendocrine tumour (NET) therapy. Materials and methods: Genome-wide screening for aberrantly methylated CGIs was performed in three NET samples, seven thymic carcinoma (TC) samples, and eight type-B3 thymoma samples. The methylation status of thymic epithelial tumours (TETs) samples was validated by pyrosequencing in a larger cohort. The expression status was analysed by quantitative polymerase chain reaction (PCR) and immunohistochemistry. Results: We identified a CGI on a novel gene, RASSF1A, which was strongly hypermethylated in NET, but not in thymic carcinoma or B3 thymoma. RASSF1A was identified as a candidate gene statistically and bibliographically, as it showed frequent CGI hypermethylation in NET by genome-wide screening. Pyrosequencing confirmed significant hypermethylation of a RASSF1A CGI in NET. Low-grade NET tissue was more strongly methylated than high-grade NET. Quantitative PCR and immunohistochemical staining revealed that RASSF1A mRNA and protein expression levels were negatively regulated by DNA methylation. Conclusions: RASSF1A is a tumour suppressor gene epigenetically dysregulated in NET. Aberrant methylation of RASSF1A has been reported in various tumours, but this is the first report of RASSF1A hypermethylation in TETs. RASSF1A may represent an epigenetic therapeutic target in thymic NET.